The Pengembangan Media Siwalan Berbasis Web dalam Pembelajaran Seni Tari di Sekolah Menengah Kejuruan (SMK) - Dwi Cahyani Putri Susrivanni; Setyo Yanuartuti; Arif Hidajad; Indar Sabri; Warih Handayaningrum (Journal of Practice Learning and Educational Development, 2026)
This study aims to develop a web-based learning media called SIWALAN (Source of Information, Insight, Meaning, and Symbol of Miyang Dance) for dance arts education at Vocational High Schools (SMK), as well as to determine students' responses to the media. The research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study are 25 students in Grade X of the Digital Business Skills Program at SMK Negeri 2 Tuban. Validation was conducted by media experts and material experts. The media expert validation received an average score of 3.82/4.00 (Highly Feasible), and the material expert scored 3.75/4.00 (Highly Feasible). The implementation test showed a very good response with an overall average score of 4.43/5.00. The highest aspect was attractiveness and motivation (4.56), followed by display quality (4.42), content quality (4.38), and ease of use (4.35). These findings confirm that the SIWALAN media effectively stimulates students' interest in traditional Tuban dance arts and is suitable for broader implementation in cultural arts education at SMK.